Endodontic Surgery/Apicoectomy - Yengoyan, Edgar; Jikia, Maia (Caucasus Journal of Health Sciences and Public Health, 2018)
Resection, or apicoectomy, of the tooth root implies its excision together with the inflamed part of the surrounding tissues. The purpose of this procedure is to stop and eliminate the odontogenic focus of infection, by removing the tumor cells that form it. Apical root end resection is becoming popular procedure as a treatment option in cases of ortho-grade endodontic failure. Apical surgery itself belongs to the field of endodontic surgery, which also includes incision and drainage, closure of perforations, and root or tooth resections. The objective of apical surgery is to surgically maintain a tooth that primarily has an endodontic lesion that cannot be resolved by conventional endodontic (re-) treatment. It is therefore of clinical relevance to perform a thorough clinical and radiographic examination of the tooth before apical surgery (including adjacent and opposing teeth), in order to decide whether surgical or non-surgical endodontics should be considered. Compared with extraction, the procedure of apicoectomy is a more gentle method and allows you to save a problem tooth. But still, do not forget that this is a real surgical operation, as a result of which specific complications may arise, and its success ultimately depends on a properly planned rehabilitation period. In order to avoid relapse and re -inflammation, in order to restore the normal way of life as soon as possible, it is necessary to comply with all the prescriptions of the doctor that will promote the best healing of the wound. Resection of the root is carried out with observation of all sanitary norms and conditions. Procedure lasts from 20 minutes to 1 hour. The duration of the manipulation depends on the location of the tooth. Easiest way to conduct an apicoectomy is on incisors and canines. More difficult is on the molars.